Royal cities in the Ararat Valley: The relationship of kingship and city through archaeological and numismatic evidence - Erhardt , Saskia; Schellig , Jessica (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
Monarchs and their royal cities have always been connected for one or more purposes, including ruling, administration, and/or pleasure. This connection was also implemented in the urban development of those cities or urban centres and can be grasped in archaeological contexts. The Ararat Valley saw an accumulation of royal cities over time, demonstrating the importance of this region for the Armenian kingdom throughout antiquity. Considering the architectural remains of known royal cities as well as philological aspects of ancient and mediaeval sources an approach to grasp the relation between cities and their rulers will be made. We add to this analysis an examination of their royal coinage. Artashat, which has been temporary capital of Armenia, was the only securely attested city in the Ararat Plain which housed a mint of the Artaxiad kings and queens (188 BCE-15 CE), plays a specific administrative role. One aim of this paper is to examine the significance of the capital mint in the currency system under the Artaxiads. Furthermore, we note the ways that the Artaxiad rulers reference the city of Artashat in their coin imagery.